2014
DOI: 10.3109/10715762.2014.895341
|View full text |Cite
|
Sign up to set email alerts
|

Maternal citrulline supplementation prevents prenatal dexamethasone-induced programmed hypertension

Abstract: Glucocorticoids are administered to premature infants to accelerate pulmonary maturation. In experimental model, prenatal dexamethasone (DEX) results in reduced nephron number and adulthood hypertension. Asymmetric dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthase (NOS), can cause oxidative stress and is involved in the development of hypertension. L-citrulline can be converted to l-arginine (the substrate for NOS) in the body. Thus we intended to determine if maternal L-citrulline ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(148 citation statements)
references
References 22 publications
3
145
0
Order By: Relevance
“…We also reported that ADMAinduced NO/reactive oxygen species (ROS) imbalance is involved in the development of hypertension in several programming models [6][7][8][9][10]. As shown in Table 2, plasma levels of L-citrulline, L-arginine and ADMA and L-arginine-to-ADMA ratio were not different between control and HF group at both 3 weeks and 3 months of age.…”
Section: Adma and Oxidative Stressmentioning
confidence: 74%
See 2 more Smart Citations
“…We also reported that ADMAinduced NO/reactive oxygen species (ROS) imbalance is involved in the development of hypertension in several programming models [6][7][8][9][10]. As shown in Table 2, plasma levels of L-citrulline, L-arginine and ADMA and L-arginine-to-ADMA ratio were not different between control and HF group at both 3 weeks and 3 months of age.…”
Section: Adma and Oxidative Stressmentioning
confidence: 74%
“…Thus, thrifty phenotype hypothesis and catch-up growth [25] might not be major mechanisms to interpret the renal programming in this model. Some particular candidate genes/pathways related to the programmed hypertension have been studied in different models of developmental programming, such as genes for nephrogenesis, oxidative stress, RAS and epigenetic regulation [2][3][4][5][6][7][8][9][10][11]. As an attempt to elucidate the impact of these candidate genes/pathways on HF-induced renal programming, we used our NGS dataset to analyze these specific groups of genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although glucocorticoids are recommended in women at risk of preterm labor to accelerate fetal lung maturation [5], emerging evidence indicates that antenatal glucocorticoids may elicit fetal programming that leads to hypertension in adulthood [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…TSC is the target of thiazide diuretics that have been most widely used as first line drugs for the treatment of hypertension in the clinic [34,35]. Recent studies showed that TSC was regulated by prenatal dexamethasone (DEX), a type of adrenocorticosteroids, and could become a new target to prevent the prenatal DEX-induced programmed hypertension by L-citrulline therapy [82].…”
Section: Pharmacogeneticsmentioning
confidence: 99%